MENINGKATKAN DAYA JUAL SECARA KOMERSIAL JAMU TRADISIONAL DESA KEMUNING MUDA KECAMATAN BUNGARAYA - Supentri Supentri; Muhammad Faisal Zam; Ricky Martin Giovanny; Silvi Eka Putri; Ajeng Atikah Merlinda; Putri Prameswari Utami; Ayu Mesa Lestari; Nur Adilah Isdawati; Enjelina Simbolon; Claudia Sinaga; Yulia Safitri (COVIT (Community Service of Health), 2022)
The economic resources of the local community in Kemuning Muda Village, Bunga Raya District, Siak Regency are agricultural, livestock, and MSME areas as a side business as well as the main business for the Kemuning Muda village community. It is important for the sustainability of the community's economy which is not low, and the people here are very enthusiastic about agriculture and agriculture and SMEs such as herbal medicine because it is easy to get traditional ingredients in making traditional herbal medicine. The thing that becomes an obstacle for traditional herbal medicine SMEs in Kemuning Muda village is that they are still less concerned about processed herbal medicine, especially from marketing. Types of traditional herbal medicine made by SMEs in the village of Kemuning Muda are herbs that are commonly found drunk by adults, teenagers, children such as kencur rice, tamarind turmeric and temulawak. The herbal medicine made by SMEs in traditional herbal medicine in the village of Kemuning Muda still uses natural ingredients and the sweetener comes from palm sugar or granulated sugar. The authenticity of the taste of traditional herbal medicine is still maintained so that the essence of traditional herbal drinks can still be felt and will damage the taste and efficacy of the traditional herbal medicine if using unnatural sweeteners. Traditional herbal medicine in Kemuning Muda village is still sold around the village or usually called jamu gendong, traditional herbal medicine in liquid form and put in bottles that will not last long. After socializing the traditional herbal medicine SMEs in the village of Kemuning Muda, who previously only knew about traditional herbal medicine and only marketed it by going around using bicycles, now they understand more about how to increase sales by way of marketing that can be recognized and recognized by the community. Keywords: traditional herbs, marketing, innovations, UMKM